Use of herbs and spices and their extracts in animal nutrition - Korošec, Tamara (Acta agriculturae Slovenica, 2009)
The ban on nutritive antibiotic use in Europe and the increased awareness of the consumers triggered a need for natural and safe feed additives to achieve better production results of farm animals. Plant extracts are used in animal nutrition as appetite and digestion stimulants, stimulants of physiological functions, for prevention and treatment of certain pathological conditions, as colorants and antioxidants. This article is a review of present literature data on the usage of plant extracts in poultry, pig and ruminant nutrition.
Keywords: animal husbandry; živinoreja; domače živali; prehrana živali; zelišča; začimbe